Geoelectric / hydrogeologic characteristics and aquifer types of ground water in the basement rocks of the area south of Zakum bello. Nasarawa state. north-central Nigeria - O. Oluyede, Kehinde (SPC Journal of Environmental Sciences, 2021)
Interpretation of vertical electrical soundings (VES) and study of lithologic logs were carried out to identify the geoelectric/hydrogeologic characteristics of the Basement Complex rocks in the area south of Zakum Bello. Geoelectric sections drawn from the interpretation results (layer resistivities and thicknesses) reveal mainly four to five layers with the first four layers constituting the weathered basement. Two aquifer types were identified. These are fractured (confined) and weathered (unconfined) aquifer. Ground water yield varies from 0.63 L/S (for the weathered layer aquifer) to 0.28 L/S (for the fractured aquifer) making the weathered basement more prolific. The fracture occurred mainly in the gneiss and thickness ranges from 5 to 10m mainly within the depth of 15 to 40m. Chemical analysis of borehole, well and stream waters which include titrimetric method for chloride and bicarbonate, UV method for nitrate and calorimetric method for sulphate shows the water to be slightly acidic and indicate good water quality throughout the area despite the variation in lithologic units. Prospective borehole sites were recommended for villages or communities without borehole.Â Â